Menerapkan Sikap Gotong Royong Bagi Peserta Didik Di Sekolah Dasar - Sunaryati, Titin; Putri, Firda Meliawati; Al Saepi, Dinar Sulis; Chandra, Nabila Azzahra (Jurnal Ilmiah Wahana Pendidikan, 2023)
Mutual Cooperation is an attitude of togetherness to achieve a goal. The purpose of this study was to see whether the school had implemented a mutual cooperation attitude to students. The method used in this research is literature study, which collects data from several references. The results that can be achieved from this observation are expected to be able to apply the attitude of mutual cooperation to students, which is important because the attitude of mutual cooperation is one of the applications of Pancasila.